RESPON GENERASI MILENIAL MUSLIM TERHADAP TRADISI KUNGKUM PURNAMA DI BANJARPANEPEN, BANYUMAS, INDONESIA - Saridin, Saridin (Asosiasi Dosen PTKIS Indonesia, 2021)
Islam entered the island of Java with the condition that the community already had a tradition. One tradition that still exists today is Kungkum Purnama in Kalicawang, Banjarpanepen Village, Sumpiuh, Banyumas District. The Kungkum Purnama tradition is carried out every year in the month of Sha'ban as a form of welcoming the month of Ramadan for Muslims. The implementation of the Kungkum Purnama tradition is followed by village communities who are not only Muslim, but also non-Muslim communities or beliefs. It is undeniable that the Muslim millennial generation is one of the inheritors of tradition. This study aims to describe the response of the Muslim millennial generation to the kungkum full moon tradition. In its implementation, the researcher uses qualitative research methods, the type of field research. Data collection was done by means of observation, interviews, and documentation. The analysis is done by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the Kungkum Purnama tradition is a form of acculturation of Islam with Banyumasan culture, which contains social and religious values, namely the symbols of Islam, to welcome Ramadan, friendship, and clean oneself. The response of the Muslim millennial generation shows their views on the kungkum full moon tradition. From a religious point of view, the practice of the full moon kungkum tradition on the other hand contains teachings that are contrary to Islamic teachings. From a cultural point of view, the full moon kungkum tradition is a local tradition and a tourist attraction that needs to be preserved. From a social point of view, the kungkum full moon tradition contains the values of cooperation, mutual cooperation, and togetherness.